The Effect of Service Quality and Trust On Community Satisfaction In Commitment Mediation In Serang Baru District, Bekasi Regency - Muhamad Dawam; Retno Purwani Setyaningrum; Sunita Dasman (Dinasti International Journal of Education Management And Social Science, 2024)
The big challenge faced by local governments in this era of globalization is how to display professional apparatus, the ability to hold bureaucratic ethics in the task of fulfilling the aspirations of the community. This study aims to determine the influence of service quality and trust on community satisfaction in commitment mediation in Serang Baru District, Bekasi Regency. The method used in this study is a quantitative method with the distribution of questionnaires and the results are processed using SmartPLS 3.0. The results of this study concluded that service quality does not have a significant influence on community satisfaction either directly or through commitment, while trust has a positive and significant influence on community satisfaction both directly and through commitment. Emphasizing the importance of increasing public trust in public services to increase public satisfaction.